2012
DOI: 10.1007/s10072-012-1274-8
|View full text |Cite
|
Sign up to set email alerts
|

Primary visual cortex excitability in migraine: a systematic review with meta-analysis

Abstract: The objective is to update and extend previous results of a systematic review of the literature with meta-analysis performed to determine the prevalence of phosphenes and the phosphene threshold (PT) values obtained during single-pulse transcranial magnetic stimulation (TMS) in adults with migraine. Both published and unpublished controlled studies measuring PT by single-pulse TMS in adults with migraine with or without aura (MA, MwA) were systematically reviewed. Prevalence of phosphenes and PT values were as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
56
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 34 publications
5
56
0
1
Order By: Relevance
“…Main findings of our electrophysiological study confirm the metaanalysis results on lower PT values obtained by circular coil TMS in migraineurs with and without aura than control subjects [20] and support the concept of an interictal visual cortical hyperexcitability in migraine patients. The pathophysiologic mechanism responsible for increased visual cortex excitability in migraine is still controversial and may be multifactorial.…”
Section: Electrophysiological Studysupporting
confidence: 86%
See 1 more Smart Citation
“…Main findings of our electrophysiological study confirm the metaanalysis results on lower PT values obtained by circular coil TMS in migraineurs with and without aura than control subjects [20] and support the concept of an interictal visual cortical hyperexcitability in migraine patients. The pathophysiologic mechanism responsible for increased visual cortex excitability in migraine is still controversial and may be multifactorial.…”
Section: Electrophysiological Studysupporting
confidence: 86%
“…A 10 cm circular coil connected to stimulator (Neurosoft, Russia; peak magnetic field = 2.2 T) was placed in a vertical position (its handle pointing upward) on the inion-nasion line, with its inferior limit 1 cm above the inion, as described before [19]. The circular coil may induce a larger electric field increasing chances of evoking phosphenes [20]. After each TMS single-pulse over visual cortex, the volunteers were encouraged to relate any sensory experiences (e.g.…”
Section: Experiments 1 (Electrophysiological Study)mentioning
confidence: 99%
“…Visual cortex hyperexcitability in migraine in response to sound-induced flash illusions, especially MWA, has been described [24]. A systematic review on transcranial magnetic stimulation studies of migraine patients supported a hyperexcitability in the primary visual cortex in MWA, but not MWOA [25]. In contrast, a recent study suggested that CSD can cause the destruction of the blood–brain barrier by activation of matrix metalloproteinase-9 [26].…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, such habituation abnormalities might be interpreted -at least for MA patients -as the result of a defective visual system inhibition (possibly, hypofunction of intracortical inhibitory circuits), rather than ''reduced preactivation'' of the visual cortex (Coppola et al, 2013). Similar considerations may extend to the occipital cortex hyperexcitability revealed by TMS studies (Brigo et al, 2013).…”
Section: Discussionmentioning
confidence: 57%
“…When considered both together, the most consistent finding was a defective habituation of pattern reversal-visual evoked potentials (PR-VEPs) (Schoenen, 2006). In turn, transcranial magnetic stimulation (TMS) provided sufficient evidence of a primary visual cortex hyperexcitability in MA (Brigo et al, 2013) whether hyperexcitability is the result of excessive excitation or defective inhibition (Coppola et al, 2007(Coppola et al, , 2013 and whether these abnormalities are exclusively attributed to MA or, conversely, to migraine in general.…”
Section: Introductionmentioning
confidence: 97%